Assessment of impact of information booklets on use of healthcare services: randomised controlled trial. Issue 7296 (19th May 2001) - Heaney, David; Wyke, Sally; Wilson, Philip; Elton, Rob; Rutledge, Philip
Abstract: Objectives: To investigate the effect of patient information booklets on overall use of health services, on particular types of use, and on possible interactions between use, deprivation category of the area in which respondents live, and age. To investigate the possibility of a differential effect on health service use between two information booklets. Design: Randomised controlled trial of two patient information booklets (covering the management and treatment of minor illness). Setting: 20 general practices in Lothian, Scotland. Participants: Random sample of patients from the community health index (n=4878) and of those contacting out of hours services (n=4530) in the previous 12 months in each of the study general practices. Intervention: Booklets were posted to participants in intervention groups (3288 were sent What Should I Do? ; 3127 were sent Health Care Manual ). Patients randomised to control group (2993) did not receive a booklet. Main outcome measures: Use of health services audited from patients' general practice notes in 12 months after receipt of booklet. Results: Receipt of either booklet had no significant effect on health service use compared with a control group. However, nine out of ten matched practices allocated to receive Health Care Manual had reduced consultation rates compared with matched practices allocated to What Should I Do? Conclusion: Widespread distribution of information booklets about the management of minor illness is unlikely to reduce demand for health services.